A comparative study on the effect of polyethylene plastic waste on sandy soils. (2018) - Chakraborty, Rupanjan; Barman, Rakesh; Bhattacharyya, Sarbajit; Das, Kuntal
Plastic pollution is one of the major global issues. Engineering measures are being undertaken to harness the non-biodegradability of plastic by converting it to a vital part of built environment. A comparative study is undertaken to evaluate the effects of the waste plastic (polyethylene) on the geotechnical properties of two locally available sands viz. Brahmaputra sand and Kulsi sand by conducting a series of direct shear tests on the two sand samples reinforced with polyethylene plastic strips. The effect of varying concentration of plastics (0.10%, 0.20%, 0.30%, 0.45%, 0.60%, 0.70% and 0.75% by weight of the sand) using different dimensions of the plastic strips is investigated. The polyethylene plastic strips' length varied from 15 mm to 45 mm and width varied from 5 mm to 15 mm. The shear strength parameters which are obtained ultimately for the composite specimens on which analysis have been done, positively reflect soil improvement due to the inclusion of polyethylene plastic waste.